2018
DOI: 10.1016/j.ejso.2018.01.090
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy as treatment option for hepatocellular carcinoma, a prospective pilot study

Abstract: Electrochemotherapy of hepatocellular carcinoma proved to be a feasible and safe treatment in all 10 patients included in this study. To evaluate the effectiveness of this method, longer observation period is needed; however the results at medium observation time of 20.5 months after treatment are encouraging, in 15 out of 17 lesions complete response was obtained. Electrochemotherapy is predominantly applicable in patients with impaired liver function due to liver cirrhosis and/or with lesions where a high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 51 publications
5
74
0
4
Order By: Relevance
“… 26 These first results show the potential of percutaneous ECT in case of Vp3-Vp4 PVTT treatment. A recently published study 94 tested, in a prospective pilot study on HCC, the effectiveness of ECT. They obtained a complete response rate of 88% per treated lesion (lesion size: 8-41 mm) and confirmed feasibility and safety, as no treatment or postoperative adverse events were recorded, even in cases with lesions located near the major hepatic vessels.…”
Section: Electrochemotherapy In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“… 26 These first results show the potential of percutaneous ECT in case of Vp3-Vp4 PVTT treatment. A recently published study 94 tested, in a prospective pilot study on HCC, the effectiveness of ECT. They obtained a complete response rate of 88% per treated lesion (lesion size: 8-41 mm) and confirmed feasibility and safety, as no treatment or postoperative adverse events were recorded, even in cases with lesions located near the major hepatic vessels.…”
Section: Electrochemotherapy In Clinical Practicementioning
confidence: 99%
“…Djokic et al 94 reported the results of a prospective study conducted in patients with HCC. Electrochemotherapy with BLM was performed on 17 HCCs in 10 patients.…”
Section: Electrochemotherapy In Clinical Practicementioning
confidence: 99%
“… 11 Recently similar results were obtained in phase I studi after ECT of hepatocellular carcinoma tumors. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The use of EP is possible and effective in any tissues; just consider that it is currently used mainly to the skin and to the subcutaneous tissue, where it has filled a "therapeutic vacuum" [10,11]. The efficacy of ECT and IRE has already been demonstrated in metastasis of non-superficial tumors, such as liver cancer [13][14][15][16][17][18][19], rectal cancer [20][21][22], primitive pancreatic cancer [23][24][25][26][27][28], esophageal tumors [28], and bone metastasis [29].…”
Section: Introductionmentioning
confidence: 99%